Patient and system factors of time to surgery after hip fracture: a scoping review - Sheehan, Katie J (BMJ Open, 2017)
OBJECTIVES: It is disputed whether the time a patient waits for surgery after hip fracture increases the risk of in-hospital death. This uncertainty matters as access to surgery following hip fracture may be underprioritised due to a lack of definitive evidence. Uncertainty in the available evidence may be due to differences in characteristics of patients, their injury and their care. We summarised the literature on patients and system factors associated with time to surgery, and collated proposed mechanisms for the associations. METHODS: We used the framework developed by Arksey and O’Malley and Levac et al for synthesis of factors and mechanisms of time to surgery after hip fracture in adults aged >50 years, published in English, between 1 January 2000 and 28 February 2017, and indexed in MEDLINE, EMBASE, CINAHL or Ageline. Proposed mechanisms for reported associations were extracted from discussion sections. RESULTS: We summarised evidence from 26 articles that reported on 24 patient and system factors of time to surgery post hip fracture. In total, 16 factors were reported by only one article. For 16 factors we found proposed mechanisms for their association with time to surgery which included surgical readiness, available resources, prioritisation and out-of-hours admission. CONCLUSIONS: We identified patient and system factors associated with time to surgery after hip fracture. This new knowledge will inform evaluation of the putative timing–death association. Future interventions should be designed to influence factors with modifiable mechanisms for delay.